Employee Benefits : - Martocchio, Joshep J. (McGraw - Hill, 2007)
This book as an introductory reference guide. Future employees/managers will gain a more complete understanding of how and why companies provide benefits as they do. The real-world focus of Martocchio’s text is evident on every page, as he seeks to balance current academic thought with brief examples of contemporary benefits practices in business.